Government Offices in Adana Province - Umar, Nur; Can, Cengiz (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2019)
Entering the Westernization process in the 18th century, the Ottoman Empire experienced the most drastic level in the 19th century. The Imperial Edict of Reorganization of 1839 led fundamental changes in the public institutions and new kinds of architectural structures emerged. While these structures varied in many areas, the first structures in the administration filed were government offices. Symbolizing state's power, these government offices made their presence felt throughout the Empire, mainly in Istanbul, in 19th century's second half. Adana and its surrounding areas emerged as the agriculture center as a result of the agricultural boost. Adana's status, which was independent state until 1864, has been changed to province in 1867. In the scope of this research, an analysis has been made on the whereabouts of these offices in the Adana Province or the prepared projects; the features of the structures; whether they have reached today or not and their current status and the problems in the preservation of them. The study was conducted in two phases: literature and achieve review and field work. In the first phase, the structures of the period of 1867-1922, as well as the structures of the period of 1922-1930 with similar genre, were determined and listed. In the second phase - lasted between 06.02.2014-15.07.2015 -a field assessment was made with the list of structures in the center and other districts. With the results, the study aims at contributing to the architectural history of the city and preservation science field.
Keywords: 19th century; Adana; government offices; architectural heritage; Architecture